The Great Age of the Car is on Its Way - Ferdinand Dudenhöffer (Wirtschaftsdienst)
Abstract Contrary to some transport scientists, we are convinced that the passenger car has a great future ahead of it. On the one hand, economic growth in many countries will boost car density, i. e. more people will be able to afford their own car. For another, strong technological innovations will drive the adaptation of passenger cars to the world of tomorrow. With electric vehicles, the industry is on the way to emission-free cars. The innovation of the intelligent and self-driving car is revolutionary. China, the most important car market in the world, is setting the pace for the introduction of autonomous driving; it is, therefore, important to partner with China.